Developing world water - Pickford, John, ed. (Grosvenor Press LondonGB, 1987)
Contains brief articles on water for the developing world. These relate to progress made during the first half of the water decade; water projects and diseases as they relate to women and children respectively; low-cost water and sanitation; voluntary agencies working in water projects; water resources; water and wastewater treatment; water in agriculture; water power, pumping and distribution; and specialist water services.